2014
DOI: 10.1155/2014/469251
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Survival Defined by the ER/PR/HER2 Subtypes and a Surrogate Classification according to Tumor Grade and Immunohistochemical Biomarkers

Abstract: Introduction. ER, PR, and HER2 are routinely available in breast cancer specimens. The purpose of this study is to contrast breast cancer-specific survival for the eight ER/PR/HER2 subtypes with survival of an immunohistochemical surrogate for the molecular subtype based on the ER/PR/HER2 subtypes and tumor grade. Methods. We identified 123,780 cases of stages 1–3 primary female invasive breast cancer from California Cancer Registry. The surrogate classification was derived using ER/PR/HER2 and tumor grade. Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
172
3
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(191 citation statements)
references
References 43 publications
10
172
3
6
Order By: Relevance
“…83 A recent study showed that the survival of patients with ER þ /PR þ / HER2 þ tumors was superior to those with ER þ /PR À /HER2 þ tumors across all stages, confirming that loss of PR is an unfavorable event. 106 These results highlighted the clinical importance of separating ER þ /PR þ /HER2 þ tumors from ER þ / PR À /HER2 þ tumors. Based on currently available data, the most commonly used IHC surrogates for luminal HER2 subtype are ER and/or PR þ /HER2 þ , which may be further divided into ER þ /PR þ /HER2 þ and ER þ /PR À /HER2 þ subtypes.…”
Section: Her2-positive Bcmentioning
confidence: 86%
“…83 A recent study showed that the survival of patients with ER þ /PR þ / HER2 þ tumors was superior to those with ER þ /PR À /HER2 þ tumors across all stages, confirming that loss of PR is an unfavorable event. 106 These results highlighted the clinical importance of separating ER þ /PR þ /HER2 þ tumors from ER þ / PR À /HER2 þ tumors. Based on currently available data, the most commonly used IHC surrogates for luminal HER2 subtype are ER and/or PR þ /HER2 þ , which may be further divided into ER þ /PR þ /HER2 þ and ER þ /PR À /HER2 þ subtypes.…”
Section: Her2-positive Bcmentioning
confidence: 86%
“…Moreover, the risk of mortality for the triple negative subgroup was at the maximum level in all stages. Inversely, the risk of luminal B/HER2+ was minimum in all stages (33). Overall, there has been increasing attention to new molecular classifications of BC, based on the genetic map (3,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), which can improve the prognostic power with low cost and high accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…Also, determination of gene expression is useful in making decisions about BC treatment (16,(20)(21)(22). In previous studies on DNA microarray in BC patients, biomolecular subtypes were assessed separately with different clinical outcomes (23).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on hormone receptors have shown that negative estrogen and progesterone receptors increase response to weakly treatment, among breast cancer patients (27,28).…”
Section: Discussionmentioning
confidence: 99%